2017
DOI: 10.1002/lno.10480
|View full text |Cite
|
Sign up to set email alerts
|

Extreme floods increase CO2 outgassing from a large Amazonian river

Abstract: Large Amazonian rivers are characteristically subject to seasonal floods. We examine how inundation extent affects the partial pressure of carbon dioxide (pCO 2 ) and CO 2 outgassing in the Madeira River, a large tributary to the Amazon River. We show data from nine field campaigns performed between 2009 and 2011, complemented with data from one additional campaign in April 2014 that is representative of the largest flood on record. Both the pCO 2 (range, 835-9694 latm) and CO 2 outgassing (range, 641-12,253 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 54 publications
8
24
0
1
Order By: Relevance
“…While our time series data support previous studies that CO 2 concentrations and fluxes vary seasonally, the frequency of our measurements further illustrated that variability was high at each site and during each measurement period. We corroborate previous studies reporting higher CO 2 concentrations and fluxes during the high water period for Amazonian rivers (Almeida et al, ; Amaral et al, ; Devol et al, ; Richey et al, ) and floodplain lakes (Abril et al, ; Rudorff et al, ). The seasonal pattern can be explained by (i) increases in water depth that increase depth integrated respiration (Devol et al, ; Forsberg et al, ) and (ii) the extent of inundation of the floodplains.…”
Section: Discussionsupporting
confidence: 92%
“…While our time series data support previous studies that CO 2 concentrations and fluxes vary seasonally, the frequency of our measurements further illustrated that variability was high at each site and during each measurement period. We corroborate previous studies reporting higher CO 2 concentrations and fluxes during the high water period for Amazonian rivers (Almeida et al, ; Amaral et al, ; Devol et al, ; Richey et al, ) and floodplain lakes (Abril et al, ; Rudorff et al, ). The seasonal pattern can be explained by (i) increases in water depth that increase depth integrated respiration (Devol et al, ; Forsberg et al, ) and (ii) the extent of inundation of the floodplains.…”
Section: Discussionsupporting
confidence: 92%
“…reported by Abril et al (2014), likely due to our surveys extending further upstream where pCO 2 was considerably higher. Receding white river (Madeira) observations are higher than those reported at the mouth ( 1300 latm) by Abril et al (2014), but lower than the 4100 latm reported further upstream by Almeida et al (2017). Clear rivers had the lowest pCO 2 of the three water types which is consistent with other studies Rasera et al 2013;Abril et al 2014).…”
Section: Co 2 and Ch 4 Distributionsupporting
confidence: 88%
“…The global organic carbon degradation by net heterotrophy of rivers and streams given by Battin et al (2008) of 0.2 PgC yr −1 is insufficient to sustain global riverine CO 2 emissions given by the most recent estimates of 0.7-1.8 PgC yr −1 (Raymond et al, 2013;Lauerwald et al, 2015), suggesting an important role of lateral CO 2 inputs in sustaining emissions to the atmosphere from rivers. In a regional et al, 2016), in sharp contrast to the extensive and sustained work that has been done on the Amazon river basin (Alsdorf et al, 2016). The Congo basin has a wide range of contrasting tributaries (differing in lithology, soil characteristics, vegetation, rainfall patterns, etc.)…”
Section: Introductionmentioning
confidence: 99%